Distributed Dynamic Packet Scheduling for Handling Disturbances in Real-Time Wireless Networks - Zhang, Tianyu; Tao Gong; Chuancai Gu; Huayi Ji; Song Han; Qingxu Deng; Hu, Xiaobo Sharon (2017 IEEE Real-Time and Embedded Technology and Applications Symposium (RTAS), 2017)
Real-time wireless networks (RTWNs) are fundamental to many Internet-of-Things (IoT) applications. Packet scheduling in an RTWN plays a critical role for achieving desired performance but is a challenging problem especially when the RTWN is large and subject to unexpected disturbances from the environment. Few solutions exist to tackle this challenge but they suffer serious limitations. This paper introduces a novel distributed dynamic packet scheduling framework, D2-PaS. D2-PaS aims to minimize the number of dropped packets while ensuring that all critical events due to disturbances are handled by their deadlines. D2-PaS builds on a number of observations that help reduce the scheduling overhead, and thus is efficient and scalable. Besides extensive simulation, D2-PaS has been implemented on an RTWN testbed to validate its applicability on real hardware. Both testbed measurements and simulation results confirm the effectiveness of D2-PaS. Compared to the best known work, D2-PaS reduces packet drop rates by 65% and 90% on average and in the best case, respectively, and also achieves 100% success for all the randomly generated task sets.